Inventarisasi Penyakit Pada Jagung (Zea mays L.) di Desa Bakung Kecamatan Indralaya Utara Kabupaten Ogan Ilir Sumatera Selatan - Tricahyati, Titi; SHK, Suparman; Hamidson, Harman; Arsi, Arsi; Agustin, Vera; Taqiyyuddin, Muhammad; Permata Sari, Yunita; Silalahi, Melda Yolanda; Anggoro Isnaini, Haidar; Ali Yahya, Irfan (Seminar Nasional Lahan Suboptimal, 2024)
Tricahyati, T., SHK., Suparman., Hamidson, H., Arsi, A., Agustin, V., Taqiyyuddin, M., Sari, Y.P.,  Silalahi, M. Y., Isnaini, H. A., Yahya, I. A. (2024). Inventory of diseases in corn (Zea mays L.) in Bakung Village, North Indralaya District, Ogan Ilir Regency, South Sumatra. In: Herlinda S et al. (Eds.),Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 711–719).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Indonesia is a country with abundant natural resources. Corn is the second main food crop after rice which is very useful for human and livestock life. This plant is also a type of grass plant with a monocotyledon seed type. However, the productivity and various benefits of corn can be disrupted by biotic and abiotic constraints. These biotic constraints are in the form of attacks by plant pests (OPT). This study aimed to evaluate the implementation of integrated OPT management used by corn farmers in Bakung Village, Indralaya District. This research method uses a purposive sampling method and farmer interviews through questionnaires. From the results of the study, three diseases were found in corn fields, namely leaf blight, leaf rust, and leaf spots. The disease samples found were then identified in the Phytopathology Laboratory of the Pest and Disease Department, Faculty of Agriculture, Sriwijaya University. Leaf blight disease is caused by the fungus Exserihilum turcicum, leaf rust disease is caused by Puccinia polysora Undrew, while leaf spot disease is caused by Helminthosporium sp. There are some farmers who implement PTT such as the application of planting distances that facilitate corn field sanitation, besides also inhibiting the transfer of pests and diseases to other corn plants. There are still many farmers who have not implemented Integrated Pest Management (IPM) and still use pesticides. Of the five farmers interviewed in Bakung Village, Indralaya District, Ogan Ilir Regency, South Sumatra, not a single farmer knew about IPM.